2006
DOI: 10.1007/s10552-006-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Age effects and temporal trends in adenocarcinoma of the esophagus and gastric cardia (United States)

Abstract: A number of hypotheses have been advanced to explain the rapid increase of the incidence of esophageal adenocarcinoma in the US. A major problem in identifying and understanding the nature of this increase is the difficulty in untangling age effects from temporal trends due to cohort and period effects. To address this problem, we have developed multi-stage carcinogenesis models that describe the age-specific incidence of adenocarcinoma of the esophagus and of the gastric cardia with separate adjustments for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 51 publications
3
48
1
1
Order By: Relevance
“…Whether the similarity of the estimated sojourn times in colon and pancreas is a general feature of epithelial cancers or mere coincidence for the two particular cancers studied here remains to be seen. However, estimates of α − β in lung (45,46), breast (W. D. Hazelton, personal communication), and Barrett's esophagus (47) suggest that clonal expansion of the earliest epithelial neoplasms is uniformly slow, ensuing with rates not too different from those found here (between 0.1 and 0.2 per year).…”
Section: Discussioncontrasting
confidence: 51%
“…Whether the similarity of the estimated sojourn times in colon and pancreas is a general feature of epithelial cancers or mere coincidence for the two particular cancers studied here remains to be seen. However, estimates of α − β in lung (45,46), breast (W. D. Hazelton, personal communication), and Barrett's esophagus (47) suggest that clonal expansion of the earliest epithelial neoplasms is uniformly slow, ensuing with rates not too different from those found here (between 0.1 and 0.2 per year).…”
Section: Discussioncontrasting
confidence: 51%
“…For all years combined, a total of 6,017 male cases (5,562 pleural, 455 peritoneal) and 1,673 female cases (1,291 pleural, 382 peritoneal) were available for the analyses. 1 We have previously presented likelihood-based analyses of the incidence of different cancers in the SEER registry using hazard functions derived from multistage models to replace the non-specific effects of age in the traditional APC models, while secular trends, i.e., period and cohort effects, were modeled in the usual fashion (see [12][13][14]). Briefly, we model the age-specific incidence (age a) occurring in calendar year j as…”
Section: Methodsmentioning
confidence: 99%
“…We discuss this model below. We also considered the two-stage clonal expansion (TSCE) model proposed by Moolgavkar and Venzon [18] and Moolgavkar and Knudson [19] and a three-stage extension of it as described in earlier papers [12][13][14]. 1 Incidence data for the same tumor can be downloaded using different coding schemes from the SEER registry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other prospective studies, mendelian randomization studies and meta-analyses confirmed the association between overweight/obesity and esophageal inflammation, metaplasia, and adenocarcinoma (17)(18)(19), according to tumorigenic mechanisms that are either dependent or independent from other risk factors, including gastroesophageal reflux and Barrett's esophagus diseases (20,21). These findings have led to speculation that obesity may represent a novel pathogenic factor involved in esophageal adenocarcinoma, so that the increase in obesity prevalence may partially explain the increase in esophageal adenocarcinoma incidence (22,23). The mechanistic link between obesity and esophageal adenocarcinoma appears to be the IGF-1 axis, together with adipocyte-secreted cytokines.…”
Section: Esophageal Cancermentioning
confidence: 87%